La creatividad como estrategia de intervención educativa en los conflictos escolares. El caso del Centro de Desarrollo Comunitario de Siloé (2004)
The following article presents the findings obtained during the intervention phase of the project titled ìCreativity and conflict resolution at schoolî, devised and developed with a group of parents, teachers, staff members, and children grades prekinder and kindergarden from the Siloé Community Development Center, located in Cali. This intervention proposal is part of the hypothesis that creativity, and more specifically symbolic mediation, allows for new forms of exchange and ways of confronting differences amongst people. This article focuses on the strategies used with 147 members of the educational community, as part of the implementation phase of research. Finally, based on the discussion of these findings, some reflections are presented in regards to the role of the different creativity levels in conflict resolution.